Effectiveness of physiotherapy exercise on shoulder's range of motion, strength, power, and pain level among ischemic stroke patients with hemiplegic shoulder pain: a review - Al-Mhanna, Sameer Badri (2020)
Introduction: Stroke is a severe form of neurological diseases which normally accompanied by hemiplegic shoulder pain. To date, studies on the effectiveness of physiotherapy exercise on shoulder's range of motion (ROM), strength, power, and pain level among ischemic stroke patients with hemiplegic shoulder is limited. Objectives: To compare shoulder’s ROM, strenght, power and pain among ischemic stroke patients with hemiplegic shoulder pain before and after following 8 weeks of physiotherapy exercise programme based on a review on previous studies from the year of 1990 to 2018. Methods: Keywords such as stroke, stroke research, stroke exercise, physiotherapist exercise for stroke and hemiplegic shoulder pain were used to find a related articles over several search platforms. Results: 338 articels were found, only 24 articles were included in the review. Based on a review, it was expected that, following exercise programme, ROM, strength, and power of both shoulders will increase. In addition, shoulders’ pain level will decrease. Conclusion: Most of the exercise programme prescribed in this review found that physiotherapy exercise improve shoulders’ range of motion, strength, power and pain level in stroke patients with hemiplegic shoulder pain.